2019
DOI: 10.1099/mgen.0.000256
|View full text |Cite
|
Sign up to set email alerts
|

Wave 2 strains of atypical Vibrio cholerae El Tor caused the 2009–2011 cholera outbreak in Papua New Guinea

Abstract: Vibrio cholerae is the causative agent of cholera, a globally important human disease for at least 200 years. In 2009–2011, the first recorded cholera outbreak in Papua New Guinea (PNG) occurred. We conducted genetic and phenotypic characterization of 21 isolates of V. cholerae , with whole-genome sequencing conducted on 2 representative isolates. The PNG outbreak was caused by an atypical El Tor strain harbouring a tandem repeat of the CTX prophage on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several other studies investigating cholera outbreak in different countries have shown that the same agent is responsible for cholera. Countries involved in the given studies are: India, V. cholerae O1 biotype El Tor serotype Ogawa 23 and V. cholerae O1, 24 Bangladesh V. cholerae O1/O139, 25 Nigeria V. cholerae O1 biotype El Tor, 26,27 Guinea V. cholerae El Tor, 28 Kenya Vibrio cholerae O1 El Tor variant, 29 and Indonesia V. cholerae O1 ST69 strains. 30 Subjects affected by the disease were found in all age groups for males and females from less than 15 years to 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies investigating cholera outbreak in different countries have shown that the same agent is responsible for cholera. Countries involved in the given studies are: India, V. cholerae O1 biotype El Tor serotype Ogawa 23 and V. cholerae O1, 24 Bangladesh V. cholerae O1/O139, 25 Nigeria V. cholerae O1 biotype El Tor, 26,27 Guinea V. cholerae El Tor, 28 Kenya Vibrio cholerae O1 El Tor variant, 29 and Indonesia V. cholerae O1 ST69 strains. 30 Subjects affected by the disease were found in all age groups for males and females from less than 15 years to 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly every Pacific island nation has identified critical environmental and public health problems resulting from the disposal of human related sewage (Brodie, 2016;Fujita et al, 2013;Naidu et al, 1991;Palanaippan et al, 2017;UNEP, 1999). These have included algae blooms and eutrophication in lagoons, deteriorating coral reef health, contaminated drinking water in wells and outbreaks of gastro-intestinal disease and cholera in human populations in contact with the polluted water (Amato et al, 2020;Barnes et al, 2019;Fujita et al, 2013;Greenhill et al, 2019;Mosley and Aalbersberg, 2003;Quimpo et al, 2020;Singh and Mosley, 2003;Yoshioka et al, 2016). Sewage pollution is considered one of the more serious human environmental problems, responsible for a high prevalence of water-related diseases (Morrison, 2016;Naidu et al, 1991;Poustie et al, 2016).…”
mentioning
confidence: 99%